(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The natural enemies of Scythia aetnensis Russo & Longo (Hemiptera, Coccidae), on Festuca circummediterranea from Mount Etna (Italy), were surveyed in 1994-5. The commonest species were the primary parasitoids Baeocharis pascuorum Mayr. and Discodes (= Phaenodiscus) aeneus (Dalman) (Hymenoptera: Encyrtidae), and the secondary parasitoids Cerapterocerus mirabilis Westwood (Hymenoptera: Encyrtidae) and Marietta picta André (Hymenoptera: Aphelinidae ). A few specimens of unidentified predators belonging to Coleoptera: Coccinellidae and Acari: Phytoseidae were also found. A first attempt to use different kinds of chromotropic traps as a parasitoid monitoring method is described.